Australia : 2007 Article IV Consultation-Staff Report; Staff Supplement; and Public Information Notice on the Executive Board Discussion. (IMF Staff Country Reports; Country Report ;, 2007)
This 2007 Article IV Consultation highlights that the lengthy expansion brought the Australian economy to a position of near full employment. Inflation had eased in late 2006 and early 2007, but accelerated in the second quarter. The current account deficit was 5 1\2 percent of GDP in 2006. The trade deficit narrowed, while the investment income balance continued to deteriorate, reflecting large net dividend payments. The Australian dollar has appreciated substantially over the past few years, but does not appear misaligned once the recent terms of trade gains are taken into account.